Influence Of Human Resource Management On Students’ Academic Performance In Public Secondary Schools In Zone A Senatorial District Of Benue State - Hauwa Ibrahim Kuku (Universitas Ahmad Dahlan, 2022)
This study investigated the influence of human resource management on students’ academic performance in education zone A of Benue State. Two research questions guided the study. Two hypotheses were formulated and tested. A descriptive research design was adopted for the study. The study population consisted of 1713 teachers in 119 secondary schools, out of which 400 teachers were sampled. Data were collected through a self-developed Questionnaire titled “Human Resource Management and Students’ Academic Performance Questionnaire (HRMSAPQ).Data were analyzed using mean and standard deviation to answer the research questions. A Chi-square test of goodness of fit was used to test the hypothesis at a 0.05 level of significance. The findings revealed a significant influence of teachers’ training on students’ academic performance in public secondary schools. The result also showed a substantial effect of teachers’ promotion on students’ academic performance in public secondary schools. It was, therefore, recommended that there is a need for the government to organize regular seminars, workshops, and in-service andconferences training to enhance productivity. Teachers should work harder to improve their knowledge and skills to be promoted to a higher level to boost their Morales to enhance students’ teaching and learning process for better performance.